Social Ontology De-dramatized. Issue 1 (January 2021) - Little, Daniel
The article responds to Richard Lauer's (2019) "Is Social Ontology Prior to Social Scientific Methodology?" The article concurs that "social ontology matters" for the conduct of research and theory in social science. It argues, however, that neither of the interpretations of the status of social ontology offered by Lauer is satisfactory (either apriori philosophical realism or pragmatist anti-realism). The article argues for a naturalized, fallibilist, and realist interpretation of the claims of social ontology and presents the field of social ontology as the most abstract edge of social-science theorizing, subject to broad empirical constraints. The approach taken is anti-foundationalist in both epistemology and metaphysics. Ontological theorizing is part of the extended scientific enterprise of understanding the social world. Claims about the nature of the social world are not different in kind from more specific sociological claims about social class or individual rationality, to be justified ultimately by the coherence and explanatory success of the theories they help to create. At the same time, it is justified to treat the claims of social ontology as provisionally true, which supports a realist interpretation of the findings of social ontology.